The Influence of Rewards and Job Training on Employee Loyalty (Case Study at PT. Limas Mulya Sentosa Kediri) - Fiorella, Kesya Sabina; Sustiyatik, Enni; Eferyn, Krissantina (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2025)
This study aims to determine the simultaneous and partial influence of Rewards and Job Training on Employee Loyalty at PT Limas Mulya Sentosa Kediri. This quantitative study aims to test the hypothesis with numerical data. All employees of PT Limas Mulya Sentosa Kediri (30 people) were sampled through saturated sampling techniques because the number of population and sample was the same. Data analysis was carried out using multiple linear regression. The results showed that rewards had a positive and significant effect on employee loyalty with a significance value of 0.004. Job training also had a significant effect with a significance value of 0.001. Simultaneously, rewards and job training had a significant effect on employee loyalty, as evidenced by the F test with a significance value of 0.000. Among the two variables, job training is the most dominant factor influencing employee loyalty, based on a higher standard beta coefficient value and lower significance than rewards. This shows the importance of job training in increasing loyalty.